The Effectiveness of Rosella Flowers to the Changes of Hemoglobin Levels of Third Trimester Pregnant Women in The Area of The RatuAgung Community Health Center in 2020 - Afrina Mizawati; Rifi Wulandari (STIKes Patria Husada Blitar, 2021)
Anemia during pregnancy is one of the most common disorders in pregnant women in Indonesia. The Government has made efforts to overcome this problem, however, the rate of anemic mothers remains high. Rosella (Hibiscus Sabdariffa) is considered able to increase the hemoglobin levels in pregnant mothers. To analyze the effect of Rosella flower on the increase of Hemoglobin level in pregnant women receiving Fe tablet. This study was a quasy experiment with pretest-posttest control group design conducted in January 2020 in the working area of Ratu Agung Community Health Center. Thirty-two participants were selected using accidental sampling, which assigned in the experiment and control group. All samples were pregnant women in the third trimester and receiving iron tablets. Independent t-test and paired t-test were used for data analysis. The paired t-test obtained a p-value of 0.00 (<0.05), indicated that there was an increase of hemoglobin levels in both experiment and control group. The mean increase of hemoglobin levels in the control group was 0.59 gr and in the experiment group was 1.11. The hemoglobin levels in the experiment group were higher than the levels in the control group. The independent t-test obtained a p-value of 0.241 (> 0.05) indicating that there wasn't a significant difference of mean of hemoglobin levels between the control group and the treatment group. The consumption of rosella combined with Fe tablet showed a significant increase of hemoglobin levels compared of pregnant women. Therefore,